AIRWAY MANAGEMENT IN EMERGENCY - Dimić, Nemanja (Halo 194 Scientific Journal of Emergency Medicine, 2020)
Airway management is crucial in the treatment of emergencies. Numerous complications can occur as a result of difficulties in airway management. The frequency of these complications is significantly higher in emergencies compared to elective surgery. Therefore, rapid assessment and adequate airway care are necessary. The most frequently used tests for assessing the airway in emergencies are the Mallampati class and the series of abbreviated procedures, which are mnemonically called LEMON. They have a significant role in predicting difficult airway management and enable adequate preparation of the medical team. In the case of an assessment of a difficult airway, it is best to follow algorithms, which, in addition to making it easier for doctors to take care of a problematic airway, also protect doctors from criminal liability if complications or death occur. In this way, taking care of the airway in emergencies can be a very serious, but not insurmountable problem.
Keywords: difficult airway management, LEMON, Mallampati, Difficult airway society algorithm